Ramón Vinyes y Jacques Gilard. Dos sabios para el Grupo de Barranquilla - José Manuel Camacho Delgado (Caravelle)
The tremendous impact that the publication of One Hundred Years of Solitude had on the world of letters was a lure to scrutinize and understand García Márquez’s personal background, from his group of friends in the Colombian coast to the teachings of playwright and storyteller from Barcelona, Ramon Vinyes, portrayed in the celebrated novel as the «Catalan Wise Man». Over nearly two decades, Professor Jacques Gilard tracked everything related to illustrious Vinyes, exiled because of Franco’s regime and mentor of García Márquez and the rest of the members of the group of Barranquilla. Through the scrutiny of newspaper archives, personal records, interviews –pencil in hand– with the last witnesses, and thanks to the access to the notebooks and diaries of the Catalan playwright, Jacques Gilard was able to rebuild the literary and existential journey of a Catalan in exile, who achieved a significant change in the course of Colombian literature.